Organizing projects with blockchain through a decentralized autonomous organization - Florian Spychiger; Michael Lustenberger; Jens Martignoni; Lukas Schädler; Patrick Lehner (Project Leadership and Society, 2023)
Blockchain and its related concept of decentral autonomous organization (DAO) is starting to influence project management. But how might project management supported by blockchain technology look like? And how would such a new form change and affect traditional project management? Not many concepts have been designed or even implemented yet. We chose an experimental framework to answer the first aspects of these questions. We developed a Decentralized Autonomous Project Organization (DAPO) and conducted an experiment to study the impact of blockchain on traditional project management. We show that such a blockchain-based approach can support the management of simple projects. Further, a fair and clear incentive scheme seems crucial and influences the way team members engage in the work. Also, more decentralized project management increases the importance of social aspects-related project management principles such as teamwork, self-organization, and cultural aspects, while principles related to budget, objectives, and schedule remain unchanged.